Implementation of Mnemonic Technique in Learning Auditing: A Classroom Experiment - Artie Ardhita Rachman; Eksa Ridwansyah; Endang Asliana (Politeknik Negeri Lampung, 2014)
The research is to empirically test the effect of using mnemonic techniques in auditing context. The ability of memorizing the auditing concept is tested through the experimental learning material. The participants involved in the experiment are the students of Accounting Study Program in Politeknik Negeri Lampung. The participants are divided into three experiment groups randomly. There are two mnemonic groups and a control group. The two mnemonic groups are a group with sentence mnemonic device and the other with first letter mnemonic device. The two devices are also tested in order to have the best device applied in auditing class. The results show that the mnemonic techniques give a positive effect in memorizing the auditing learning material, with the sentence mnemonic device as the best technique.Keywords: Experiments, Auditing Concept, Mnemonic